Efficient adsorption and full spectrum photocatalytic degradation of low concentration PPCPs promoted by graphene/TiO2 nanowires hybrid structure in 3D hydrogel networks. Issue 45 (21st July 2020) - Hu, Yajie; Yang, Yanan; Zhang, Jiejing; Jin, Shengnan; Zheng, Hong
Abstract : A 3D rGO/GNW hydrogel exhibits efficient adsorption, full spectrum photocatalytic performance and significant potential for low concentration PPCP removal from water. Abstract : The removal of low concentration PPCPs from water is a challenging issue. A graphene hydrogel with 3D networks shows great potential for accelerating eddy diffusion of low concentration PPCPs. Herein, to further promote its molecular diffusion, a graphene/TiO2 nanowires (GNW) hybrid structure was implanted into graphene hydrogel. The as-prepared rGO/GNW hydrogel exhibited significantly enhanced adsorption–photocatalytic performance and excellent stability for low concentration ethenzamide, a typical pharmaceutical pollutant in water, under vacuum ultraviolet (VUV), ultraviolet (UV), visible and near-infrared light irradiation. When the initial ethenzamide concentration was 500 ppb and catalyst dosage was 10 mg/150 mL, ethenzamide was completely removed in 3 min and the corresponding photocatalytic apparent rate constant was 2.20 times that by GNW, 4.09 times that by rGO/P25 and 4.31 times that by rGO/NW under VUV irradiation, respectively, and its removal rate attained 99.0% in 120 min and the corresponding photocatalytic apparent rate constant was 2.06 times that by GNW, 3.34 times that by rGO/P25 and 17.42 times that by rGO/NW under UV irradiation, respectively. The GNW hybrid structure in the hydrogel played a vital role in overcoming the mass transfer resistance of low concentration PPCPs. The as-prepared rGO/GNW hydrogel exhibits significant potential for the removal of low concentration PPCPs from water.